Changes in the Management of Common Bile Duct Stones: 1980 to Date - Ruth Stalnikowicz; Jochanan Benbassat (Rambam Maimonides Medical Journal, 2024)
Objective: To compare the results of treating patients with common bile duct (CBD) stones by endoscopic sphincterotomy (ES), surgical exploration, or a combination of ES and surgical CBD exploration (the rendezvous technique).